2020
DOI: 10.15441/ceem.19.081
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultra-low cost fitness trackers as clinical monitors in low resource emergency departments

Abstract: In low resource hospitals, strained staffing ratios and lack of telemetry can put patients at risk for clinical deterioration and unexpected cardiac arrest. While traditional telemetry systems can provide real-time continuous vital signs, they are too expensive for widespread use in these settings. At the same time, developed countries such as the United States have been increasingly utilizing remote monitoring systems to shift patient care from hospital to home. While the context is dramatically different, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To support the latter point, wrist-worn smartbands have been tested and validated in different clinical and home-monitoring settings and have been always found as well-tolerated tools. [51][52][53] Another advantage of commercial smartbands over selfreported questionnaires is the long-term data storage and their suitability to retrospective studies. Users' data collected through Fitbit Inc.'s and similar devices can be indefinitely stored within the manufacturer's server, and thereby retrieved through the API provided by the company.…”
Section: Discussionmentioning
confidence: 99%
“…To support the latter point, wrist-worn smartbands have been tested and validated in different clinical and home-monitoring settings and have been always found as well-tolerated tools. [51][52][53] Another advantage of commercial smartbands over selfreported questionnaires is the long-term data storage and their suitability to retrospective studies. Users' data collected through Fitbit Inc.'s and similar devices can be indefinitely stored within the manufacturer's server, and thereby retrieved through the API provided by the company.…”
Section: Discussionmentioning
confidence: 99%
“…The healthcare industry is increasingly focused on continuous health monitoring , and public health threats. Although commercial wearables such as smart watches and fitness trackers have become popular for health monitoring in recent years, , there remain challenges concerning the real-time acquisition of accurate versatile physiological information. This has led to the development of health-monitoring sensors with specific characteristics, such as multifunctionality, real-time monitoring, and skin conformability.…”
Section: Health-monitoring Sensorsmentioning
confidence: 99%
“…Smartbands have come to the medical community’s attention as tools capable of collecting biomarkers information, and therefore to monitor patients’ health status. Their role has been investigated in oncology, where they were tested as a tool for the activity tracking in breast cancer survivors (Chung et al., 2019 ), and in emergency departments, where they were tested for the low‐cost heart rate (HR) monitoring in critical patients (Dagan & Mechanic, 2020 ). Both studies concluded that commercial Smartbands are a feasible tool for HR monitoring in these two different circumstances.…”
Section: Introductionmentioning
confidence: 99%